2022
DOI: 10.7759/cureus.26255
|View full text |Cite
|
Sign up to set email alerts
|

Sudden Cardiac Death Risk Perception and Its Relation to Personal Lifestyle Among Female University Students During the COVID-19 Pandemic

Abstract: IntroductionRisk perception is the key component of many health behavior changes. This study identified the deliberative sudden cardiac death (SCD) risk perception among young females during the coronavirus disease 2019 (COVID-19) pandemic and its implication on their willingness to lifestyle change in the Riyadh region, Saudi Arabia. This cross-sectional study using self-administered online questionnaires was conducted to reach a total of 797 female university students in Riyadh, Saudi Arabia. ResultsEighty-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(8 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“… 17 , 21 Additionally, the perception of risk may be influenced by other factors, such as personal experience, media coverage, and cultural beliefs, which may not be directly related to income. 21 , 28–30 …”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“… 17 , 21 Additionally, the perception of risk may be influenced by other factors, such as personal experience, media coverage, and cultural beliefs, which may not be directly related to income. 21 , 28–30 …”
Section: Discussionmentioning
confidence: 99%
“…In terms of physical activity and risk perception, our study found that inactive participants perceived less risk compared to active participants, which is consistent with previous studies. 21 , 28 , 37 However, variations in findings across different studies might be attributed to differences in sample characteristics, and future studies could consider utilizing data from smartwatches for more accurate results. 41–43 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations